Keynote address at the American Society of Breast Surgeons 18th Annual Meeting: current and future application of Intraoperative Radiotherapy (IORT) in the curative and palliative treatment of breast cancer - Wenz, Frederik (Annals of surgical oncology, 2017)
Intraoperative radiotherapy (IORT) is increasingly used worldwide. Breast cancer is the most rapidly growing indication for IORT, approaching 70-80% of cases in most centers. This report reviews the theoretical background and clinical use of IORT for primary and metastasized breast cancer. There are established applications such as tumor bed boost during breast-conserving surgery followed by whole breast radiotherapy or IORT as a form of accelerated partial-breast irradiation (APBI) for selected patients. Novel applications such as IORT for vertebral or brain metastases are presented as well as technological developments, widening the spectrum of potential clinical applications for IORT.